(untitled) (Journal of Dhaka Medical College, 2010)
A 30 years old male presented with fever, headache, myalgia, anorexia, petechial haemorrhage, easy bruising, gum bleeding and purpuric rash. Initially it appeared to be a case of autoimmune thrombocytopenic purpura (ITP) but finally our patient was diagnosed as a case of immune thrombocytopenia due to hepatitis B-virus infection. In this report we document the immune thrombocytopenic purpura (ITP) in a 30 years old male patient which is due to hepatitis B-virus infection in the replicative phase. Assessment of the replicative status and activity of liver disease of the patient was done. Key words: Immune Thrombocytopenic Purpura (ITP); Hepatitis B-Virus Infection. DOI: 10.3329/jdmc.v19i1.6259 J Dhaka Med. Coll. 2010; 19(1) : 72-73.